PENALARAN DALAM TUTURAN LISAN GURU PADA PEMBELAJARAN DI SMP KOTA MALANG - Ribut Wahyu Eriyanti (Faculty of Languages and Arts, Universitas Negeri Yogyakarta, 2017)
AbstractThis study aims to describe reasoning patterns and strategies in teachers’ language in learning at junior high schools (JHSs) in Malang City. The study used the qualitativephenomenological approach. The subjects were teachers of the Indonesian language,Science, Mathematics, and Social Studies in two public JHSs and two private JHSs inMalang City. The data were collected through observations supported by video recordingdevices. The results of the study are as follows. First, the reasoning patterns in teachers’language in learning consist of: (1) Topic + Comment and Comment + Topic patterns inthe sentence level; (2) (a) Main Idea (MI) + Supporting Materials (SM), (b) SM + MI, (c)SM + MI + Further Supporting Materials (FSM), and (d) SM + Implied Main Idea (IMI)in the fragment level; and (3) (a) MI + SM, (b) SM + MI + SM + MI, (c) SM + MI + SM + MI+ SM, and (d) MI + SM + MI in the discourse level. Second, the reasoning strategies inteachers’ language in learninginclude: (1) deductive strategies with examples, both directand analoguos ones; (2) inductive strategies; and (3) mixed (convergent) strategies.Keywords: reasoning, teachers’ language, learning, construction